Coordinated Portfolio Investment Survey Guide (second edition). (Manuals and Guides, 2002)
This paper reviews the coordinated portfolio investment survey (CPIS) guide. The objectives of CPIS are to collect comprehensive information, with geographical detail on the country of residence of the issuer, on the stock of cross-border equities, long-term bonds and notes, and short-term debt instruments for use in the compilation or improvement of international investment position statistics on portfolio investment capital. This paper discusses the scope and modalities of the CPIS. It also presents key findings of the 1997 CPIS and 2001 CPIS.